Anomalous Raman scattering and lattice dynamics in mono- and few-layer WTe2. Issue 4 (11th January 2016) - Kim, Younghee; Jhon, Young In; Park, June; Kim, Jae Hun; Lee, Seok; Jhon, Young Min
Abstract : The evolution of Raman spectrum of WTe2 from bulk to monolayer (left). Optical image of a WTe2 flake containing mono- to tri-layer regions and Raman intensity maps of the A1 3 and A1 4 modes (middle). Atomic visualization for the lattice vibration in the A1 7 mode that occurs in the direction of tungsten chains (right). Abstract : Tungsten ditelluride (WTe2 ) is a layered material that exhibits excellent magnetoresistance and thermoelectric behaviors, which are deeply related with its distorted orthorhombic phase that may critically affect the lattice dynamics of this material. Here, we report comprehensive characterization of Raman spectra of WTe2 from bulk to monolayer using experimental and computational methods. We find that mono and bi-layer WTe2 are easily identified by Raman spectroscopy since two or one Raman modes that are observed in higher-layer WTe2 are greatly suppressed below the noise level in the mono- and bi-layer WTe2, respectively. In addition, the frequency of in-plane A1 7 mode of WTe2 remains almost constant as the layer number decreases, while all the other Raman modes consistently blueshift, which is completely different from the vibrational behavior of hexagonal metal dichalcogenides. First-principles calculation validates experimental results and reveals that anomalous lattice vibrations in WTe2 are attributed to the formation of tungsten chains that make WTe2 structurally one-dimensional.